Role of Integrated Digital Systems in Cash Transaction Recording: Operational Practices at BYD Arista Pondok Indah - Mikha Prima Yolenta; Siti Magfiroh (Journal of Innovative and Creativity, 2026)
Cash, as the most liquid asset, plays a crucial role in business continuity, requiring accurate and traceable recording supported by reliable information systems. The rise of digitalization has encouraged companies to shift from manual processes to integrated digital systems, including Enterprise Resource Planning (ERP). This study aims to describe the role of integrated digital systems in recording cash transactions at BYD Arista Pondok Indah by examining the use of the Arista Dealer Management System (ADMS) and Odoo ERP. A qualitative descriptive case study approach was employed, with data collected through direct observation, work participation, informal interviews with system users, and review of internal documentation. The results indicate that cash receipts and disbursements are processed non-cash and documented digitally from operational activities to financial reporting through the integration of ADMS and Odoo. While the digital system serves as the main tool for data recording and integration, the effectiveness of cash recording depends on user roles, data accuracy, and inter-functional coordination. Future research will expand the study scope and combine descriptive and quantitative analyses to evaluate the quality and effectiveness of cash information produced.